"I am the heart? I am only a nail, growing on a dead body": Individuality Destroyed and Rebuilt in Yitzhak Laor's Ephraim Returns to the Army - Latowicki, Tali (MiKAN, 2006)
This article follows the intertextual character of the play EphraimReturns to the Army, and reads it through other works mentioned in itor alluded to, along with Laor's works in other genres. The intertextualstrategy has a clear political function of de-mystification. However,it also carries a powerful emotional potential, derived from thecorrelations it draws between the hero of the play and the impliedplaywright, encouraging the reader to identify both of them withYitzhak Laor himself. Precisely because of the obvious link betweenthe author and his hero, it is meaningful that the political ending ofthe play, with its utopian alternative to the current power relations, isrealized only after the disappearance of the male protagonist from thestage. Only then is a new subjectivity constructed - out of the femalecharacter whose traits greatly resemble the attacked female addresseein Laor's erotic poems. Thus the stage seems to supply Laor with theutopian space necessary to realize the political and sexual ׳Other', butonly at the price of the metaphorical death of the male hero.